2013
DOI: 10.1007/s40136-013-0025-6
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Robotic Surgery for Otolaryngology

Abstract: As minimally invasive surgery has become common in head and neck surgery, the role of robotic surgery has expanded from thyroid surgery and transoral robotic surgery (TORS) of the oropharynx and supraglottic to other areas. Surgeons have advanced the limits of TORS, adapting lasers to the Da Vinci robot for glottic cancer, and combining existing techniques for transoral supraglottic laryngectomy and hypopharyngectomy to perform transoral total laryngectomy. Skull base approaches have been reported with some su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…45 However, the role of the da Vinci robot has increased dramatically because of additional developments and refinements, and it has been used for a wide range of procedures in the head and neck. [51][52][53] There are intraoperative issues that are specific to TORS. Previous studies have reported a setup time of 15 to 19 minutes, with an operative time of 39 to 84 minutes, depending on the exact procedure and experience level of the team.…”
Section: Transoral Robotic Surgerymentioning
confidence: 99%
“…45 However, the role of the da Vinci robot has increased dramatically because of additional developments and refinements, and it has been used for a wide range of procedures in the head and neck. [51][52][53] There are intraoperative issues that are specific to TORS. Previous studies have reported a setup time of 15 to 19 minutes, with an operative time of 39 to 84 minutes, depending on the exact procedure and experience level of the team.…”
Section: Transoral Robotic Surgerymentioning
confidence: 99%
“…This system, developed for use in thoracoscopy and laparoscopy, utilizes rigid 3D high‐definition angled and linear endoscopes in combination with robotic arms, and offers many unique aspects, including endowrist movement and tremor filtering . The da Vinci system is not without challenges though, most notable the system's large footprint and rigid, linear scopes, which limits its access to regions in the head and neck that cannot be exposed via “line‐of‐sight.” Flexible endoscopes to visualize around the curves of the tongue base and pharynx have previously been used for biopsies and surveillance but until recently could not be used for surgical resection secondary to the lack of tension/counter tensions required for resection.…”
Section: Introductionmentioning
confidence: 99%
“…TLM has well documented acceptable oncologic outcomes, and interim functional and disease-control data have indicated that TORS can additionally be a safe, useful, and cost-effective component in the approach to a variety of conditions in the head and neck [5,10,17,[23][24][25][26]. There are ongoing efforts to further document the value of both TLM and TORS and expand the clinical application of these techniques.…”
Section: Introductionmentioning
confidence: 99%